Gingival mesenchymal stem cell‐derived exosomes are immunosuppressive in preventing collagen‐induced arthritis. Issue 3 (24th December 2021) - Tian, Xiaohong; Wei, Wumei; Cao, Yue; Ao, Tianrang; Huang, Feng; Javed, Rabia; Wang, Xiaohong; Fan, Jun; Zhang, Yanhui; Liu, Yanying; Lai, Laijun; Ao, Qiang
Abstract: Due to the unsatisfied effects of clinical drugs used in rheumatoid arthritis (RA), investigators shifted their focus on the biotherapy. Although human gingival mesenchymal stem cells (GMSC) have the potential to be used in treating RA, GMSC‐based therapy has some inevitable side effects such as immunogenicity and tumorigenicity. As one of the most important paracrine mediators, GMSC‐derived exosomes (GMSC‐Exo) exhibit therapeutic effects via immunomodulation in a variety of disease models, bypassing potential shortcomings of the direct use of MSCs. Furthermore, exosomes are not sensitive to freezing and thawing, and can be readily available for use. GMSC‐Exo has been reported to promote tissue regeneration and wound healing, but have not been reported to be effective against autoimmune diseases. We herein compare the immunomodulatory functions of GMSC‐Exo and GMSC in collagen‐induced arthritis (CIA) model and in vitro CD4 + T‐cell co‐culture model. The results show that GMSC‐Exo has the same or stronger effects compared with GMSC in inhibiting IL‐17A and promoting IL‐10, reducing incidences and bone erosion of arthritis, via inhibiting IL‐17RA‐Act1‐TRAF6‐NF‐κB signal pathway. Our results suggest that GMSC‐Exo has many advantages in treating CIA, and may offer a promising new cell‐free therapy strategy for RA and other autoimmune diseases. Abstract : Gingival mesenchymal stem cell‐derived exosomes (GMSC‐Exo) ameliorate inflammation and bone erosion of metatarsophalangeal joint through regulating CD4 + T cells, which mainly by suppressing the differentiation of Th1 and Th17 cells while promoting Treg cells differentiation. Simultaneously, GMSC‐Exo also inhibit IL‐17RA‐NF‐κB signal pathway to exert their therapeutic effects in collagen‐induced arthritis.